Getting Started with Microbiome Analysis: Sample Acquisition to Bioinformatics. (15th July 2014) - Kumar, Ranjit; Eipers, Peter; Little, Rebecca B.; Crowley, Michael; Crossman, David K.; Lefkowitz, Elliot J.; Morrow, Casey D.
Abstract: Historically, in order to study microbes, it was necessary to grow them in the laboratory. It was clear though that many microbe communities were refractory to study because none of the members could be grown outside of their native habitat. The development of culture‐independent methods to study microbiota using high‐throughput sequencing of the 16S ribosomal RNA gene variable regions present in all prokaryotic organisms has provided new opportunities to investigate complex microbial communities. In this unit, the process for a microbiome analysis is described. Many of the components required for this process may already exist. A pipeline is described for acquisition of samples from different sites on the human body, isolation of microbial DNA, and DNA sequencing using the Illumina MiSeq sequencing platform. Finally, a new analytical workflow for basic bioinformatics data analysis, QWRAP, is described, which can be used by clinical and basic science investigators. Curr. Protoc. Hum. Genet . 82:18.8.1‐18.8.29. © 2014 by John Wiley & Sons, Inc.